ACCELERATING THE DISSEMINATION OF DA'WAH VALUES THROUGH HADROH CULTURE ON INSTAGRAM - M. Fajar Ramadhan; Hasan Sazali (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze efforts to accelerate the dissemination of Islamic preaching messages and values in the hadroh culture on Instagram, focusing on Hadroh Darusshofa Medan's Islamic preaching and its Instagram as a digital Islamic preaching medium. The method used in this study is qualitative to intensively understand the communication patterns, strategies, and communication that occur between the actors and audiences of Islamic preaching in digital media. The results of the study indicate that the acceleration of Islamic preaching dissemination does not focus on changing the content of values, but rather on how to adapt the media, strategies, and communication methods that are tailored to the characteristics of the audience in the digital era. Hadroh Darusshofa Medan combines conventional Islamic preaching or bil-lisan with a blend of musical art, visual aesthetics, and communication accommodations that can increase audience appeal and engagement. The use of Instagram as a digital Islamic preaching medium has been proven to help Islamic preaching expand its reach and encourage audiences to participate actively, as described in the theory of communication accommodation and the theory of uses and gratifications. However, challenges arise in balancing the sacred values of Islamic preaching with the demands of fast, and competitive digital content.  This study confirms that the integration of culture, digital technology, and adaptive communication strategies is key to increasing the effectiveness and relevance of da'wah in the modern era.